Obtaining and Characterization of New Materials - Sandu, Andrei Victor (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
At present, more and more procedures and technologies used to discover and characterize new materials are available, including advanced characterization techniques.This Special Issue covers a wide range of topics about obtaining and characterizing new materials, from the nano to macro scales, including for new alloys, ceramics, composites, biomaterials, and polymers and the procedures and technologies used to enhance their structure, properties, and functions. To select new materials for future use, we must first understand their structure and their characteristics using modern techniques such as microscopy (SEM, TEM, AFM, STM, etc.), spectroscopy (EDX, XRD, XRF, FTIR, XPS, etc.), and mechanical tests (tensile, hardness, elastic modulus, toughness, etc.) and their behaviors (in vitro and in vivo; corrosion; and thermal-DSC, STA, DMA, magnetic properties, and biocompatibility), among many others.